2019
DOI: 10.1111/jpn.13148
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid profiles of muscle and liver tissues of Australian Merino, Damara and Dorper lambs under restricted feeding

Abstract: Seasonal weight loss (SWL) is a major constraint in extensive animal production systems in the tropics and Mediterranean. The objective of this study was to characterize the amino acid profile of muscle and hepatic tissues of Australian Merino, Damara and Dorper lambs under restricted feeding to evaluate the impact of SWL at the metabolic and physiological levels. SWL induced generalized muscle protein breakdown among restricted groups of all breeds, with varying intensity. Dorper breed mobilized less muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Mineral profiling has been extensively studied before, in the most varied contexts and species (Almeida et al, 2006; Giuffrida‐Mendoza, Arenas de Moreno, Uzcátegui‐Bracho, Rincón‐Villalobos, & Huerta‐Leidenz, 2007; Lérias et al, 2016; Mahmud, Rehman, Anwar, & Ali, 2011). This particular study has been performed at the end of a series of previously published papers (Almeida et al, 2013; Almeida et al, 2016; Ferreira et al, 2017; Miller et al, 2019; Palma, Scanlon, et al, 2016; Ribeiro, Madeira, et al, 2019; Scanlon et al, 2013) which allows the interaction of our results to others concerning SWL and tissue proteomics, metabolomics, amino acid quantification, animal performance and meat quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral profiling has been extensively studied before, in the most varied contexts and species (Almeida et al, 2006; Giuffrida‐Mendoza, Arenas de Moreno, Uzcátegui‐Bracho, Rincón‐Villalobos, & Huerta‐Leidenz, 2007; Lérias et al, 2016; Mahmud, Rehman, Anwar, & Ali, 2011). This particular study has been performed at the end of a series of previously published papers (Almeida et al, 2013; Almeida et al, 2016; Ferreira et al, 2017; Miller et al, 2019; Palma, Scanlon, et al, 2016; Ribeiro, Madeira, et al, 2019; Scanlon et al, 2013) which allows the interaction of our results to others concerning SWL and tissue proteomics, metabolomics, amino acid quantification, animal performance and meat quality.…”
Section: Resultsmentioning
confidence: 99%
“…It has an important impact on animal production systems in these areas, as supplementary feed is often necessary if not indispensable to prevent loss of production (Almeida et al, 2013). This phenomenon has been studied in goat bucks (Almeida, Schwalbach, Waal, Greyling, & Cardoso, 2006), sheep (Almeida et al, 2013, 2016; Ferreira et al, 2017; Miller et al, 2019; Ribeiro, Madeira, et al, 2019; Scanlon et al, 2013) and dairy goats (Hernández‐Castellano et al, 2016; Lérias et al, 2013, 2015; Palma, Hernández‐Castellano, et al, 2016). Specifically, Scanlon et al (2013) have reported sheep performance of Australian Merino, Damara and Dorper lambs.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, the sustainability of farming systems will rely on their ability to cope with a reduction of external inputs such as concentrate and other feed resources. In this context, a better understanding of the relationship between the nutrients supply, nutritional status, their interactions with BR dynamics and the progression of the metabolic profile is essential for the development of more comprehensive nutrition managements of animals based on their relative adaptive capacities [ 20 , 21 , 22 , 23 , 24 ]. The objectives of this study were to evaluate and describe how dietary energy restrictions and/or repletion influences change in BW, BCS and metabolic status responses in Merinos d’Arles ewes, considered to be a robust, rustic and hardy sheep breed.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to highlight that we focused on the energy density of the diets; however, one may expect that experimental treatments also induced different protein balances between the diets, which were also likely affecting, even if indirectly, the overall animal responses. Our approach is different (and complementary) to that used by other authors more focused in mineral and protein metabolism mechanisms (including nutrient uptake and mobilization in muscle and hepatic tissues) explaining sheep’s ability to withstand weight loss [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is the primary stress hormone in ruminants [38] and Sheep and goat breeds that are indigenous to the semi-arid tropical regions display higher thermotolerance in temperatures of 40 • C and 42 • C by increasing cortisol production [10,48]. An increase in cortisol levels in response to heat stress causes protein catabolism to provide glucogenic amino acids utilized in gluconeogenesis [49]. This is, however, not a reliable indicator of heat stress, since not all studies in small ruminants show elevation of plasma levels of cortisol.…”
Section: Thermoregulatory Mechanisms In Small Ruminantsmentioning
confidence: 99%